Tantangan dan Pencegahan Radikalisme di Indonesia - Fatmawati, Indah; Faisal Primadiansyah, Arivianda; Gyska Krisna Mukti, Muhammad; Adam Nugroho, Ahmad; Ahmad, Hilyan; Aulia Muthmainnah, Nasywa (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
Radicalism is a global phenomenon that also enters and spreads throughout the territory of the Republic of Indonesia. This phenomenon has a significant impact on social, political, and security stability. The spread of radicalism is usually characterized by extreme perspectives that support rapid fundamental change and often use violent means. The history of radicalism in Indonesia covers various phases, ranging from the Darul Islam movement after independence to the expansion of radical groups in the reform era that utilized technology and social media as propaganda and recruitment. Triggering factors for radicalism in Indonesia include socio-political dissatisfaction, religious sentiments, anti-Westernism ideology, and suboptimal government policies. The characteristics of radical groups include exclusivity, fundamentalism, acting hard, and having a tendency to disbelieve others. These challenges finally encourage researchers to contribute their thoughts to face them. This research further wants to describe the challenges and efforts to prevent radicalism in Indonesia. This research is a type of library research that is descriptive. The conclusion of this study shows that the challenges and efforts that can be carried out in dealing with radicalism in Indonesia must be holistic, namely through education based on Pancasila values, strengthening solidarity and tolerance, and reducing social disparities. Community participation is also the key to success in preventing the spread of radicalism, including by reporting radical activities and filtering information on social media. The collaboration of all elements is also expected to be able to stop the exposure to radicalism that spreads in Indonesia.